2014
DOI: 10.1556/avet.2013.038
|View full text |Cite
|
Sign up to set email alerts
|

Mixed infection by fowlpox virus and Chlamydophila psittaci in a commercial laying hen flock

Abstract: An outbreak of fowlpox occurred in a commercial laying hen flock in one of the western provinces of Poland. Clinical signs suggested fowlpox and the diagnosis was confirmed by histopathological detection of Bollinger bodies within the epithelial cells. Detailed ultrastructural examination revealed an additional concurrent infection with chlamydia-like particles. The particles were identified by PCR as fowlpox virus and Chlamydophila psittaci. It is worth noting that both pathogens can generate morphologic form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…It is probable that some interventions may induce more stress for birds and lead to heavier shedding, but this cannot explain all the differences in the prevalence or the excretion level in birds and other factors, such as the "outdoor" factor, that seem to critically impact shedding ( Table 1). As has been previously reported, the presence of coinfections could exacerbate chlamydial shedding (27)(28)(29)(30). Unlike the cases described in these latter studies, it is interesting that the herpesvirus infection that emerged in flock A2 (resulting in premature slaughtering) did not increase the level of C. psittaci shedding from ducks, which therefore had the same shedding pattern as those of flock A1.…”
Section: Discussionsupporting
confidence: 57%
“…It is probable that some interventions may induce more stress for birds and lead to heavier shedding, but this cannot explain all the differences in the prevalence or the excretion level in birds and other factors, such as the "outdoor" factor, that seem to critically impact shedding ( Table 1). As has been previously reported, the presence of coinfections could exacerbate chlamydial shedding (27)(28)(29)(30). Unlike the cases described in these latter studies, it is interesting that the herpesvirus infection that emerged in flock A2 (resulting in premature slaughtering) did not increase the level of C. psittaci shedding from ducks, which therefore had the same shedding pattern as those of flock A1.…”
Section: Discussionsupporting
confidence: 57%
“…Virus and bacteria often act synergistically in causing diseases in humans or animals. C. psittaci -avian pneumovirus co-infection has been associated with an outbreak in turkeys [12] , C. psittaci -fowlpox virus co-infection with an outbreak in hens [9] and C. psittaci -reovirus with an outbreak in budgerigars [11] . Infectious bursal disease virus and chicken anaemia virus can cause immunosuppression, leading to secondary bacterial infection such as bacterial chondronecrosis with osteomyelitis [43] .…”
Section: Discussionmentioning
confidence: 99%
“…Large human outbreaks are rare even among bird handlers [8] . Although co-infection of C. psittaci and viruses has been reported in outbreaks of avian species [9] [12] , no virus-bacterium co-infection of implicated avian species has ever been reported in outbreaks of human psittacosis. In this study, we sought to investigate viruses that cause avian co-infection, which may have led to this outbreak of psittacosis.…”
Section: Introductionmentioning
confidence: 99%
“…C. psittaci has caused respiratory and systemic infections in birds and continues for a long time under unfavorable conditions, and chlamydia parrot and other pathogens can cause mixed infection in birds and poultry [8]. A great number of reports have indicated that virus and bacteria often act synergistically in causing diseases in humans or animals.…”
Section: Introductionmentioning
confidence: 99%